"Because I said so!": Mothers' conventional conflict justifications related to resolution and child behavior problems and temperamental reactivity. (May 2021) - Tollossa, Ruhama M.; Nelson, Jackie A.
A common strategy parents use to justify their point of view during parent–child conflict is conventional reasoning, which focuses on child obedience to authority. In this brief report, we examined mothers' use of conventional justification during mother–child conflict discussions in relation to the resolution reached and children's behavior problems and temperamental reactivity concurrently and longitudinally. Participants included 190 mothers and their 5- to 7-year-old children. Dyads engaged in a conflict discussion task in the laboratory, which was coded for mothers' use of conventional justification and the type of resolution reached. Mothers reported on child behavior problems and temperamental reactivity then and 1 year later. Results showed mothers used more conventional reasoning during conflict discussions that resulted in a win/loss resolution compared to a compromise. Mothers' conventional reasoning was concurrently associated with more child externalizing behaviors and temperamental reactivity at Year 1. Mothers' conventional reasoning did not relate to changes in child behaviors over time. Findings are discussed in terms of mothers' conceptions of parental authority and possible directions of effects.